Penerapan Building Information Modeling (BIM) Pada Bangunan Gedung Bertingkat Menggunakan Tekla Structures - Aditya, Wawan; Purwandito, Meilandy; Fauzia, Arisna (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Building Information Modeling (BIM) is a digital representation that has transformed the way the construction industry operates through the digitalization and digital data management. This advancement digitalization is also supported by the Ministry of Public Works and Housing (PUPR) through Ministerial Regulation number 22/PRT/M/2018, which mandates the use of BIM methods in the construction of state buildings with more than two floors. The BIM Implementation Policy in PUPR infrastructure development, published by the Research and Development Center for Policy and Technology Application in 2019. The success of construction projects is determined by the accuracy of quality, time, and cost, both in the planning and construction stages. The research object is the multi-story lecture building of the Faculty of Economics at Universitas Samudra. The study was conducted by modeling the building structure using Tekla Structures, then comparing the Bill of Quantity (BOQ) generated by the BIM concept with the BOQ calculated manually. Data were obtained from the planning documents Detail Engineering Design (DED) and BOQ by the Planning Consultant, referring to the SNI 2847:2019 standard Requirements for Structural Concrete for Buildings. The research results show that the comparison of BOQ work using the BIM method on structural components produced a concrete volume of 432.20 m³ (97.26%), a deformed bar weight of 44,138.38 kg (90.49%), and a plain bar weight of 37,023.87 kg (97.09%) of the planned calculation. The differences obtained are due to the different calculation methods in BIM, manual calculation errors (human error), and rebar detailing calculations using general equations.